Wisata Gastronomi Makanan Tradisional Yogyakarta melalui Storynomic - Nugroho, Setyo Prasiyono (Media Wisata, 2023)
A Storynomics Tourism is a new style in promoting tourism and the country's creative economy. Innovation with a storynomics tourism approach is expected to attract foreign tourists to Indonesia. The storynomics tourism approach will help build tourists' interpretation and imagination of a tourist attraction. Apart from legends or folklore, storynomics tourism can also start from historical stories. A place or traditional food with a big historical story has the potential to be developed using a storynomics tourism approach to attract tourists. The aim of this research is to find out the origins of Yogyakarta traditional food which can be used as a storynomic, and to find out the methods of processing Yogyakarta traditional food, in order to increase the number of tourist visits and to preserve Yogyakarta traditional food. This research method consists of in-depth interviews, observation, documentation and literature study. This research is a qualitative descriptive study. The population and sample in this study were ten main foods and snacks as well as five traditional drinks typical of Yogyakarta. Next, in-depth interview techniques were used to find out the origins of Yogyakarta traditional food as well as the use of ingredients and processing methods for this traditional food. Furthermore, the informants in this research were historians or gastronomists from the Center for the Conservation of Cultural Values in the city of Yogyakarta and traditional food producers in the city of Yogyakarta as additional informants. Then, the analysis technique in this research uses the research method developed by Milles and Hubberman (2006), which consists of data reduction, data presentation and drawing conclusions or verification. The results of the research show that traditional food in five sub-districts in Yogyakarta on average has a story behind its preparation, and traditional processing methods are still maintained to this day.